2015
DOI: 10.1093/abbs/gmv022
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of a trypsin inhibitor from the seeds of <italic>Artocarpus heterophyllus</italic> Lam.

Abstract: A proteinaceous inhibitor against trypsin was isolated from the seeds of Artocarpus heterophyllus Lam. by successive ammonium sulfate precipitation, ion-exchange, and gel-filtration chromatography. The trypsin inhibitor, named as AHLTI (A. heterophyllus Lam. trypsin inhibitor), consisted of a single polypeptide chain with a molecular weight of 28.5 kDa, which was confirmed by sodium dodecyl sulfate-polyacrylamide gel electrophoresis and gel-filtration chromatography. The N-terminal sequence of AHLTI was DEPPSE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
3
3
0
Order By: Relevance
“…These results taken together suggest that one of the reactive sites of PnBBI is flexible to bind either trypsin or chymotrypsin. Similar binding ratio (1:2) was reported earlier in case of TIs isolated from L. albus (Scarafoni et al, 2008), Vigna mungo (Prasad et al, 2010b), Artocarpus heterophyllus (Lyu et al, 2015) and Psophocarpus tetragonolobus (Banerjee et al, 2017).…”
Section: Biochemical and Biophysical Characterization Of Macromoleculsupporting
confidence: 89%
“…These results taken together suggest that one of the reactive sites of PnBBI is flexible to bind either trypsin or chymotrypsin. Similar binding ratio (1:2) was reported earlier in case of TIs isolated from L. albus (Scarafoni et al, 2008), Vigna mungo (Prasad et al, 2010b), Artocarpus heterophyllus (Lyu et al, 2015) and Psophocarpus tetragonolobus (Banerjee et al, 2017).…”
Section: Biochemical and Biophysical Characterization Of Macromoleculsupporting
confidence: 89%
“…The band estimated at 16 kDa may also be from the ArtinM polypeptide chains (Cecílio et al, 2016;Pranchevicius et al, 2012). The band with an estimated molar mass of 28.5 kDa is possibly the same that Lyu et al (2015) reported in their work as a trypsin inhibitor purified from jackfruit seeds. The determined molecular masses agree with those found by Kabir (1995), Vijayakumar and Forrester (1986) and Moreira and Oliveira (1983) for the subunits of the lectins from jackfruit they isolated by ion-exchange, affinity and molecular sieve chromatography.…”
Section: Capture Of Lectinssupporting
confidence: 80%
“…Lectins are also found in a variety of organisms, from bacteria to animals (Santana et al, 2008;Perçin and Aksöz, 2012). Jackfruit is a tropical tree of the family Moraceae that produces large-sized fruits Its potential for protein extraction has been reported in numerous studies, as is the case for lectins, proteases and protease inhibitors (Cecílio et al, 2016;Gangaraju et al, 2015;Lyu et al, 2015;Swami et al, 2012;Siritapetawee and Thammasirirak, 2011). Lectins are the main proteins found in jackfruit seeds and jacalin accounts for about 50% of their total protein content (Swami et al, 2012;Kabir, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The purification of LsCTI by a single chromatography step achieved a 0.88% protein yield. LsCTI recovery was lower than those reported for Butea monosperma (7.7%) and Artocarpus heterophyllus (7.1%) protease inhibitors, but higher than that of Pipitadenia moniliformis (0.15%) …”
Section: Resultssupporting
confidence: 65%
“…The lower K i value for LsCTI obtained for chymotrypsin is consistent with its higher affinity for that enzyme. The LsCTI K i value for trypsin was higher than those for BmPI from B. monosperma (1.2 x 10 ‐9 m ) and IVTI from Inga vera (1.19 x 10 ‐9 m ), but the K i value for chymotrypsin was similar in magnitude to those for the inhibitor from Ricinus communis (1.9 x 10 ‐8 m ) and AHLTI from A. heterophyllus (3.47 x 10 ‐8 m ) …”
Section: Resultsmentioning
confidence: 99%